The Social Skills and Relationship with Family Climate in the Early Childhood (A descriptive study on A Syrian sample) - Saud, Alaa Ahmed Tawfiq; Abdullah, Muhammad Qasim (Journal of Educational and Psychological Sciences, 2021)
The Research aims to Identifying the relationship between the Social Skills and the family climate, Exploring the differences in the Social Skills according to the gender variable and the birth order, in addition to identifying the differences in the family climate according to the economic level of the family. to achieve the research goals, a tool has been applied for measuring the family climate and the social skills on a sample consists of (712) mothers of children aged 3- 6 years in Syria.Research result showed There is a positive correlation between the social skills and the family climate, There are statistically significant differences in the social skills according to the gender variable, no significant differences in the social skills according to the birth order, in addition to there are statistically significant differences in the family climate according to the economic level of the family
Keywords: The social skills; Family climate; Early childhood